1991
DOI: 10.7326/0003-4819-114-6-445
|View full text |Cite
|
Sign up to set email alerts
|

Sulphasalazine and Prednisone Compared with Sulphasalazine for Treating Active Crohn Disease

Abstract: The use of prednisone in addition to sulphasalazine in patients with active Crohn disease results in a significantly faster initial improvement, but not in a significantly better result after 16 weeks of treatment, when disease activity is measured by the Van Hees Activity Index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…These results were confirmed in other smaller studies [13, 14]. Details on these studies are provided above, in the SFS section.…”
Section: First-line Treatment Optionssupporting
confidence: 80%
See 1 more Smart Citation
“…These results were confirmed in other smaller studies [13, 14]. Details on these studies are provided above, in the SFS section.…”
Section: First-line Treatment Optionssupporting
confidence: 80%
“…Other smaller trials confirmed that SFS 3–6 g/day is superior to placebo in mild-to-moderate CD [11, 12]. In other well-designed studies, SFS showed no adjunctive effect on prednisone and no steroid-sparing effect [13], while prednisone has an adjunctive effect on SFS [14]. In one uncontrolled retrospective analysis, Goldstein et al [15 ]estimated that about 25% of patients with disease limited to the small bowel benefit from long-term SFS therapy.…”
Section: First-line Treatment Optionsmentioning
confidence: 70%
“…These results were confirmed in other smaller studies [12, 13]. Details about these studies are provided above, in the SFS section.…”
Section: First-line Treatment Optionssupporting
confidence: 80%
“…Other smaller trials have confirmed that SFS 3–6 g/day is superior to placebo in mild to moderate CD [10, 11]. In other well-designed studies, SFS showed no adjunctive effect on prednisone and no steroid-sparing effect [12], while prednisone has an adjunctive effect on SFS [13]. In one uncontrolled retrospective analysis, Goldstein et al [14] estimated that about 25% of patients with disease limited to the small bowel benefit from long-term SFS therapy.…”
Section: First-line Treatment Optionsmentioning
confidence: 99%
“…ere are no short-or long-term bene ts from the addition of aminosalicylates to corticosteroids (92,125,126) . Azathioprine and 6-mercaptopurine have had demonstrable adjunctive bene ts to steroids in adults (number needed to treat (NNT) = 5) (127,128) .…”
Section: Mild To Moderate Active Diseasementioning
confidence: 99%